Qualitative assessment of groundwater in an area in the Sinawon region (Journal of Libya for geographical studies, 2024)
This study aims to evaluate the quality of groundwater in the Libyan Sinawun region and find out its chemical properties. Seven samples of groundwater wells in the region were collected with varying depths of these wells, which included most of the residential neighborhoods in the region. Then chemical tests were conducted for them, represented by the amount of pH and total salts.  Solid and dissolved salts, as the percentage of salts was high, exceeding the permissible limit according to the Libyan specifications. It reached 7960 mg/L in the Muhammad al-Bakush well, while in the main Sinawun well it reached 1150 mg/L. This means that the values ​​exceeded the permissible limit according to the Libyan specifications and standards.  While the samples recorded an increase in the percentage of total hardness, reaching 3599 mg/L in the Muhammad al-Bakoush well. As for calcium, its percentage ranged between 110-740 mg/L, and the magnesium percentage varied, as it was recorded in the main Sinawun well at 48.6 mg/L.  Muhammad Al-Bakoush well: 415 mg/L, which means that depth has an impact on water quality for the Sinawon region.
Keywords: Groundwater; chemical analysis; geographic information systems; pH; standards